2018
DOI: 10.3389/fbioe.2018.00186
|View full text |Cite
|
Sign up to set email alerts
|

How Synthetic Biology and Metabolic Engineering Can Boost the Generation of Artificial Blood Using Microbial Production Hosts

Abstract: Hemoglobin is an essential protein to the human body as it transports oxygen to organs and tissues through the bloodstream (Looker et al., 1992). In recent years, there has been an increasing concern regarding the global supply of this vital protein, as blood availability cannot currently meet the high demands in many developing countries. There are, in addition, several risks associated with conventional blood transfusions such as the presence of blood-borne viruses like HIV and Hepatitis. These risks along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Hemoglobins have been adopted as acellular oxygen transporters, iron supplying agents and coloring and flavoring agents in the food industry. The use of recombinant human hemoglobin as an oxygen carrier in the production of artificial blood, for example, has been an alternative explored to meet the demand for blood transfusions worldwide [172][173][174]. Myoglobin is an important contributor to the sensory quality of meat, related to the red tone and metallic flavor.…”
Section: Flavoring Proteinsmentioning
confidence: 99%
“…Hemoglobins have been adopted as acellular oxygen transporters, iron supplying agents and coloring and flavoring agents in the food industry. The use of recombinant human hemoglobin as an oxygen carrier in the production of artificial blood, for example, has been an alternative explored to meet the demand for blood transfusions worldwide [172][173][174]. Myoglobin is an important contributor to the sensory quality of meat, related to the red tone and metallic flavor.…”
Section: Flavoring Proteinsmentioning
confidence: 99%
“…The first-in-human phase I clinical trial from 2020 to assess HbV’s safety and pharmacokinetics in healthy male adult volunteers found that HbV is safe and efficacious. HbV can potentially be used as an alternative to allogeneic blood transfusion as well as for oxygen and carbon monoxide therapy, perfusate for transplant organs, and photosensitizer [ 15 , 28 , 29 ]. Permission for a Phase I clinical trial was also granted to Dr. Sakai’s group in Japan [ 28 ].…”
Section: Past and Present Hboc Products Approved For Clinical Trialsmentioning
confidence: 99%
“…The World Health Organization believes that synthetic biology and the development of engineering techniques have provided unique opportunities for global scientists to make promising hemoglobin production [ 29 ]. The various diverse and complex challenges, believed to be insurmountable, will be overcome with new developments in powerful synthetic biomedical and genetic engineering technologies [ 29 ].…”
Section: Past and Present Hboc Products Approved For Clinical Trialsmentioning
confidence: 99%
“…The availability of site-directed mutagenesis techniques has enabled the production of recombinant human Hb variants targeted at specific functions. Today, engineered Saccharomyces cerevisiae or Corynebacterium glutamicum strains can produce up to 18-20% of total cell proteins as human Hb [154,155] at reasonable costs and high yields: a single 100 m 3 tank may produce 200 kg of Hb, i.e., the equivalent of 1300 L of blood [156]. Observing the characteristics of naturally occurring human Hb mutations provides lessons on how to design recombinant Hb [157].…”
Section: Recombinant Hbmentioning
confidence: 99%